O impacto de programas de educação cívica promovidos pelo poder legislativo como política pública institucional para formação cidadã: lições a partir do Parlamento Jovem mineiro - Cardozo, Denise (Universidade Federal de São Carlos, 2022)
The thematic questioning of this study guides the need to face the resumption of the debate of the so-called "institutional confidence crisis", analyzes the conjectures to investigate the relationship regarding the knowledge and the attrition scenario of Brazilian institutions and politics, and directs the project to examine the contribution of public policies to civic education programs developed by the Legislative Houses in Brazil. The research used a quantitative and almost experimental method, through data from a survey of the Young Parliament Program of the Legislative Assembly of Minas Gerais (PJ), 2008 edition, which promoted two rounds of questions (pre-test and post-test ) between two groups: young participants (treatment) and young non-participants (control). The study tested the relationship between citizenship and civic culture on issues related to knowledge, behavior and participation in democracy. In conclusion, the data initially made it possible to sustain premises of failures in civic education; confirm that activities improve the image of trust in the brazilian institution, fact already found in the literature in this regard; and, consolidate concepts that drive research on education such as citizen transformation and democratic support. However, the data also allowed us to reflect on the fragility of this first edition of the program (PJ) as it did not obtain results on broader knowledge of political sophistication and did not immediately impact behaviors such as adherence to democracy, trust in other institutions and interest in politics among the young participants. On the other hand, it also allowed us to reflect on the impact that the Program (PJ) had as an example of transforming public policy, as it was a role model for the institution of this type of program in thousands of other legislative houses, assemblies and municipal councils, even gaining a national program at the Congress. It also allowed a very important compendium of research, which later tested, in broader periods, the immediate and late effects that this important type of instrument can contribute to citizen education and the strengthening of democracy.
The impact of civic education programs promoted by the legislature as an institutional public policy for citizen education: lessons from the Young Minas Gerais Parliament
Keywords: Cidadania; Democracia; Educação cívica; Citizenship; Democracy; Civic education; CIENCIAS HUMANAS::CIENCIA POLITICA; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO::ATITUDE E IDEOLOGIAS POLITICAS; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::SOCIOLOGIA DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS::ANALISE INSTITUCIONAL